A review on puncture analysis of polymer composites. (2021) - Mansoor, Shaik; Vasudevan, A.; Ravikumar, M.M.
Abstract: This study projects the behaviour of polymer composite when it is tested under different shape of tools under different loads. The impact on the polymer material is subjected to continuous change accordingly by changing the loads and shapes acting on it. The results are examined to what extent the polymer material can withstand the resistance of penetration of tool through the composite material. This can be helpful in further developments for implementation in military applications and air craft materials. The experiment has its importance in military vests usage because of its advantages of low weight and resistance, it could be carried easily and comfortably which could save valuable lives of soldiers. The objective is to find out the material strength against penetration of sharp and different shaped objects with different velocities. The tools used for puncture analysis of polymer composite are stainless steel-316 in the shapes of 1-Flat indenter, 2-Conical indenter, 3-Hemispherical indenters, 4-elliptical indenter. A bottom fixture is made along with same stainless steel-316 for placing the polymer materials on its top where the testing surface for puncture analysis. The results are monitored and analysed with the help of universal testing machine. Nearly 20 components are tested for different data outcome so that the variations in results can be observed for a suitable composite with suitable composition. The materials here also include the usage of Sandwich composites, polyurethane materials, epoxy fibre, adhesives, silicon nano particles. These all the materials are combinedly used for making the material suitable for experimenting. The materials have been selected based on characteristics of materials, strengths, reliability with cost effective manners. The outcome of this experimental project would give us a clear information of further details of usage for different materials and their outcomes. Therefore, the classification of materials can be made easy due to availability of results which leads to sophisticated developments in their designs.